(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2024)
Background: Guillain-Barré Syndrome (GBS) is an acute immune-mediated polyradiculoneuropathy which is one of the most frequent causes of acute flaccid paralysis. GBS has diverse clinical phenotype and functional outcome. Objective: The purpose of the present study was to evaluate clinical profiles and outcomes of GBS patients admitted in a tertiary care centre of Bangladesh. Methodology: This prospective cohort study was conducted in the Department of Neurology from January 2016 to June, 2020 in BIRDEM General Hospital, Dhaka, Bangladesh. Adult patients more than or equal to 18 years of age who had fulfilled the diagnostic criteria of GBS were included in the study. Results: Majority of the patients were male (64.0%). The most common presenting symptom at entry was ascending paralysis that occurred in 24 patients (48.0%). Mean age of the study population is 31.5 years ranging from 19 to 60 years. Twenty four (48.0%) patients had GBS disability score of 4 at entry. On the contrary, 39(78.0%) cases had GBS disability score of 4 at nadir. Diarrhea was reported in 14(28.0%) cases and respiratory tract infection was reported in 9(18.0%) cases. Fifty six percents of patients had GBS disability score of 0 to 2, 38.0% had 3 to 4 and only 6.0% had 5 to 6. Majority of the patients had Brighton criteria level 1 certainty of diagnosis (62.0%) in this study. GBS variants according to nerve conduction studies were AIDP (54.0%), AMAN (34.0% and AMSAN (12.0%). CSF protein was raised in 72.0% cases. Patients diagnosed with AMAN and AMSAN had worse outcome after 3 months in comparison to AIDP group of patients if we consider GBS disability score. Conclusion: GBS has been found more in younger and male population group in this present study where Antecedent events were not found in majority of the patients. AIDP was the commonest variant in our study with comparatively good outcome followed by AMAN. Journal of National Institute of Neurosciences Bangladesh, July 2023;9(2):108-115